Implementasi Kebijakan Diversity, Equity, and Inclusion di Industri Teknologi - Novrianzah, M. Rustam; Andrias, Mone Stephanus (Universitas Mercu Buana, 2025)
This research is motivated by the importance of implementing Diversity, Equity, and Inclusion (DEI) policies in the Indonesian technology industry, especially in Software as a Service (SaaS) companies operating in Jakarta, and the need to increase innovation and global competitiveness through a more inclusive and diverse work environment. The main problems identified are how employees perceive and experience DEI policies, and the challenges faced in implementing them in a heterogeneous and dynamic work environment. This research uses a qualitative approach with a case study design at PT. Cloud, where data is collected through in-depth semi-structured interviews with employees from various backgrounds, positions, and work experiences. Data analysis was carried out thematically, strengthening data validity by source triangulation. The results indicate that the DEI policy implemented in the PT Cloud entity has created a more inclusive and supportive work atmosphere. Cultural bias and resistance at the structural level are a challenge to solve. Overall, the implementation of DEI increases job satisfaction, motivation, and collaboration between teams.